2020
DOI: 10.1101/2020.01.20.912105
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Selective germline genome edited pigs and their long immune tolerance in Non Human Primates

Abstract: Organ transplantation is the only curative treatment for patients with terminal organ failure, however, there is a worldwide organ shortage. Genetically modified pig organs and tissues have become an attractive and practical alternative solution for the severe organ shortage, which has been made possible by significant progress in xenotransplantation in recent years.The past several decades witnessed an expanding list of genetically engineered pigs due to technology advancements, however, the necessary combina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…A summary of GMs proposed for xeno-organ donor pigs is provided in Table 1 . Progress in gene editing technologies facilitated the generation of pigs carrying several of these GMs (reviewed previously 93 ), in some cases up to 11 94 or 12. 95 We focus here on the combinations that have been tested in heterotopic or orthotopic HTx experiments in baboons (Section 3).…”
Section: Pathobiology Of Pig Organ Xtx and Concepts For Gm Of Donor Pigsmentioning
confidence: 99%
“…A summary of GMs proposed for xeno-organ donor pigs is provided in Table 1 . Progress in gene editing technologies facilitated the generation of pigs carrying several of these GMs (reviewed previously 93 ), in some cases up to 11 94 or 12. 95 We focus here on the combinations that have been tested in heterotopic or orthotopic HTx experiments in baboons (Section 3).…”
Section: Pathobiology Of Pig Organ Xtx and Concepts For Gm Of Donor Pigsmentioning
confidence: 99%
“…Recently, a genetically engineered pig with 11 modifications was reported. 40 The modifications were introduced in 2 steps: first, GGTA1 , CMAH , and B4GALNT2 were simultaneously knocked out using CRISPR/Cas9. Second, the triple knockout cells were cotransfected with 3 PiggyBac vectors harboring multigene expression cassettes (hCD46/hCD55/hCD59, hTHBD/hTFPI/hCD39, and HLA-E/hCD47) and PiggyBac transposase.…”
Section: Pigs As Organ Donors—physiological and Immunological Aspectsmentioning
confidence: 99%
“…Promoters for ubiquitous expression seem to be suitable for expressing human complement regulating genes and immune-cell response factor genes, such as CD46, CD55, human HLAs, and CD47. The ICAM2 promoter has been frequently used for specific expression of anti-coagulation and anti-inflammatory proteins, including tissue factor pathway inhibitor (TFPI), thrombomodulin (THBD), C1 inhibitor, and A20 [ 3 , 19 , 20 ]. In previous studies, we reported the production of GTKO pigs carrying human CD46 (GTKO/CD46) or THBD (GTKO/CD46/THBD) driven by the CMV promoter [ 21 , 22 ], CAG promoters for ubiquitous expression, and the pig ICAM2 promoter for endothelium-specific expression of THBD and CD73 [ 23 ].…”
Section: Discussionmentioning
confidence: 99%